2011
DOI: 10.1248/jhs.57.540
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Intracellular Ca2+ Level by Triclosan in Rat Thymic Lymphocytes: Increase in Membrane Ca2+ Permeability and Induction of Intracellular Ca2+ Release

Abstract: Triclosan is an antibacterial agent used in household items and personal care products. Because wild animals and humans can harbor this compound in their systems, the toxic effects of triclosan are a possibility and are suspected. Therefore, we examined the effects of triclosan on intracellular Ca 2+ concentration in rat thymocytes by cytometric techniques using fluorescent probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the present study, we found that triclosan increased cytosolic [Ca 2+ ] i in vascular smooth muscle cells (A10 cells). There are several studies showing that triclosan is able to alter/elevate intracellular free Ca 2+ levels in animal and human cell lines 3 , 18 . Cherednichenko et al 17 reported that triclosan depressed excitation–contraction coupling, inhibited L-type Ca 2+ currents, and Ca 2+ transients in cardiac muscle, indicating that the regulation of triclosan on Ca 2+ signals in smooth muscle and cardiac muscle was through distinct mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that triclosan increased cytosolic [Ca 2+ ] i in vascular smooth muscle cells (A10 cells). There are several studies showing that triclosan is able to alter/elevate intracellular free Ca 2+ levels in animal and human cell lines 3 , 18 . Cherednichenko et al 17 reported that triclosan depressed excitation–contraction coupling, inhibited L-type Ca 2+ currents, and Ca 2+ transients in cardiac muscle, indicating that the regulation of triclosan on Ca 2+ signals in smooth muscle and cardiac muscle was through distinct mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Triclosan (TCS), 5-chloro-2-(2,4-dichloro phenoxy) phenol, is an endocrine-disrupting chemical often used as an antiseptic, disinfectant, or preservative [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the European Union, 85% of triclosan is used in personal care products (e.g., soaps, toothpaste, mouthwash, and cosmetics), and 10% in plastics and food contact materials (household utensils), while the remaining 5% is used in textiles (antibacterial clothing) [ 1 , 2 , 3 , 4 , 5 , 11 ]. It is also used as a suture coating, but only contributes 0.00016% of the overall TCS global exposure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%